Implementing web-based language learning to improve grammar skills of junior high school students: Grammar monster - Murtiningsih Sri Rejeki; Zulfa Auliya Failaih; Sudarsi Sri; Ariebowo Teguh; Darmi Ramiaida (E3S Web of Conferences)
This research aims to determine the effectiveness of web-based language learning (WBLL) in improving junior high school students’ grammar. An experimental quantitative study method was applied in this research among 50 junior high school students from experimental and control groups. The data collection technique used grammar test questions consisting of 25 questions. All students will take the pre-test and post-test, and WBLL will intervene the experimental group after the pre-test is conducted. The grammar website used in this study is Grammar Monster. The findings from statistical analysis show that the experimental and control groups demonstrate significant differences. The experimental group experienced an increase after the intervention using web-based language learning compared to the control group, which experienced a decrease in the post-test score. The results of the independent sample t-test showed a sig 2 (tailed) of 0.002, which is smaller than 0.05. It can be interpreted that WBLL, especially Grammar Monster web, can improve the mastery of grammar in English learning. The study found significant improvements in grammar skills in the experimental group, demonstrating WBLL is effectiveness. This research addresses the gap in the literature regarding the underutilization of WBLL tools in junior high education.